High Ductility in a fully martensitic microstructure: a paradox in a Ti alloy produced by selective laser melting. Issue 11 (2nd November 2018) - Zafari, A.; Xia, K.
ABSTRACT: A fully martensitic Ti alloy consisting entirely of hexagonal-close-packed α ′ was produced by selective laser melting (SLM), exhibiting an impressive combination of high strength and excellent ductility. A small quantity of body-centred-cubic β formed at some large primary α ′ plates oriented at ∼45° to the tensile direction was found responsible for early fracture owing to α ′/ β strain incompatibility. Properly selected SLM parameters resulted in a β -free microstructure containing α ′/ α ′ interfaces only, preventing premature fracture. Consequently, large plastic deformation was enabled, creating randomly oriented nano- α ′ crystals. The investigation dispels the myth that α ′ is inherently brittle. GRAPHICAL ABSTRACT: Impact Statement: A fully martensitic α ′ Ti-6Al-4V with an impressive combination of high ductility and strength was produced using selective laser melting, dispelling the myth that α ′ is inherently brittle.